2017
DOI: 10.1080/13506285.2017.1370430
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric organization in disorders of development

Abstract: A recent theoretical account posits that, during the acquisition of word recognition in childhood, the pressure to couple visual and language representations in the left hemisphere (LH) results in competition with the LH representation of faces, which consequently become largely, albeit not exclusively, lateralized to the right hemisphere (RH). We explore predictions from this hypothesis using a hemifield behavioral paradigm with words and faces as stimuli, with concurrent ERP measurement, in a group of adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 61 publications
1
30
1
Order By: Relevance
“…For example, research in developmental and acquired prosopagnosia suggests that impairments in face recognition can occur even as visual processing of words is normal (Susilo et al 2015;Rubino et al 2016;Burns et al 2017). In contrast, the "many-to-many" view, which suggests shared neural circuits for word and face processing, predicts that developmental deficits for faces and words will co-occur (Behrmann and Plaut 2013;Collins et al 2017). Additionally, developmental theories (Behrmann and Plaut 2015;Dehaene et al 2015) have also suggested that the interactive development of face and word processing is due to competition on foveal resources, resulting in the left lateralization of word information and the right lateralization of face information (Behrmann and Plaut 2015;Dehaene et al 2015;Gomez et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, research in developmental and acquired prosopagnosia suggests that impairments in face recognition can occur even as visual processing of words is normal (Susilo et al 2015;Rubino et al 2016;Burns et al 2017). In contrast, the "many-to-many" view, which suggests shared neural circuits for word and face processing, predicts that developmental deficits for faces and words will co-occur (Behrmann and Plaut 2013;Collins et al 2017). Additionally, developmental theories (Behrmann and Plaut 2015;Dehaene et al 2015) have also suggested that the interactive development of face and word processing is due to competition on foveal resources, resulting in the left lateralization of word information and the right lateralization of face information (Behrmann and Plaut 2015;Dehaene et al 2015;Gomez et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Related studies in individuals with prosopagnosia have focused on the P300 ERP to rare faces and have shown intact novelty detection [22], even when earlier visual ERPs such as the P100 are slower than those elicited from the healthy controls [23]. We also note that, just as in acquired prosopagnosia, there have been studies using ERP in individuals with congenital prosopagnosia and, again, these studies have focused primarily on the N170 component [20,24,25].…”
Section: Introductionmentioning
confidence: 98%
“…Recent advances in neuroscience, however, have shown anatomical irregularities in the development, connectivity, or lateralisation of left occipitotemporal regions associated with visual processing (for review see: Ramus et al, ). Remarkably, visual processing per se is not routinely assessed in DD, but when it has been, impairments are apparent and in some instances without a phonological deficit (Behrmann & Plaut, ; Collins, Dundas, Gabay, Plaut, & Behrmann, ; Dundas, Gabay, Plaut, & Behrmann, ; Dundas, Plaut, & Behrmann, ; Gabay, Dundas, Plaut, & Behrmann, ). Moreover, the visual deficit is not restricted to words and extends to other visual stimuli (for a recent theoretical proposal see: Behrmann & Plaut, ; Plaut & Behrmann, ).…”
Section: Introductionmentioning
confidence: 99%